The NORMATYWNE I DOKTRYNALNE PODSTAWY KSZTAŁTOWANIA SIĘ IDEI ODRĘBNEGO POSTĘPOWANIA ZE SKAZANYMI UZALEŻNIONYMI OD ALKOHOLU W POLSCE W LATACH 1918–1969 - Kryński, Marcin Józef (Civitas et Lex, 2021)
The aim of the article is to present the idea of ​​a separate treatment of alcohol-dependent convicts in the interwar period. It also attempts to answer the question which concepts of polish penitentiary representatives have found recognition and formed a basis of the newly created legal regulations. Due to the fact that the polish penitentiary system was taken over after the annexations and was based on various principles of operation, considerations regarding the creation of the idea of ​​separate treatment of alcohol-dependent convicts were preceded by a description of the polish penitentiary system. When assessing the organization of the polish penitentiary system of the Second Republic of Poland, it should be taken into account that a significant problem was the lack of financial resources and the prisons taken over after invaders required significant investments. The historical conditions of that time forced to build the penitentiary system from scratch, not in an evolutionary way. For this reason, the newly adopted legal regulations were based on postulates developed by polish penitentiary representatives, and the treatment of alcohol-dependent convicts was a component of the reform of imprisonment execution in the Second Polish Republic.